Gender differences in competitiveness and fear of failure help explain why girls have lower life satisfaction than boys in gender equal countries - Eriksson, Kimmo; Strimling, Pontus (Frontiers in Psychology, 2023)
Among 15-year-olds, boys tend to report higher life satisfaction than girls. Recent research has shown that this gender gap tends to be larger in more gender-egalitarian countries. We shed light on this apparent paradox by examining the mediating role of two psychological dispositions: competitiveness and fear of failure. Using data from the 2018 PISA study, we analyze the life satisfaction, competitiveness, and fear of failure of more than 400,000 15-year-old boys and girls in 63 countries with known levels of gender equality. We find that competitiveness and fear of failure together mediate more than 40 percent of the effects on life satisfaction of gender and its interaction with gender equality. Thus, interventions targeting competitiveness and fear of failure could potentially have an impact on the gender gap in life satisfaction among adolescents in gender equal countries.